2021
DOI: 10.1590/s1517-707620210003.13013
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do comportamento reológico de pastas de cimento com adição de óxido de grafeno

Abstract: RESUMO A adição de óxido de grafeno (OG) em materiais cimentícios permite a obtenção de compósitos mais resistentes e duráveis, com menor carga de poluentes associada à sua produção. Pesquisas anteriores demonstraram que a adição de nanomateriais à pasta de cimento pode provocar o aumento nos parâmetros reológicos de viscosidade e limite de escoamento. Este estudo teve como objetivo investigar as alterações no comportamento reológico de pastas de cimento devido à adição de OG. De forma a cumprir este objetivo,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…HORTA et al (9) summarize the reason for the reductions observed in the fluidity of the paste with nanomaterials addiction to three main factors: i) the tendency of nanomaterials to agglomeration, due to the van der Waals interactions between the sheets, resulting in less fluidity of the cementitious materials; ii) the high specific surface area of the material, which, when added to cement pastes, causes an increase in the demand for water needed to wet its surface, thus reducing the water content available for lubrication; iii) when accounting for the water in the nanomaterial suspension in the mix of cement pastes, the volume of mixing water must be reduced to keep the water/cement ratio fixed. As a result, there is an evident reduction in the water content available to involve the cement grains, making the paste more viscous (9; 14; 15).…”
Section: Introductionmentioning
confidence: 99%
“…HORTA et al (9) summarize the reason for the reductions observed in the fluidity of the paste with nanomaterials addiction to three main factors: i) the tendency of nanomaterials to agglomeration, due to the van der Waals interactions between the sheets, resulting in less fluidity of the cementitious materials; ii) the high specific surface area of the material, which, when added to cement pastes, causes an increase in the demand for water needed to wet its surface, thus reducing the water content available for lubrication; iii) when accounting for the water in the nanomaterial suspension in the mix of cement pastes, the volume of mixing water must be reduced to keep the water/cement ratio fixed. As a result, there is an evident reduction in the water content available to involve the cement grains, making the paste more viscous (9; 14; 15).…”
Section: Introductionmentioning
confidence: 99%